Harnessing the power of technology for the treatment and prevention of eating disorders. Issue 5 (9th May 2013) - Bauer, Stephanie; Moessner, Markus
Abstract Objective: The objective of this article is to review the available literature regarding the development and evaluation of technology‐enhanced interventions for eating disorders. Method: Literature was reviewed pertaining to interventions that use technology (e.g., Internet, mobile phones) for prevention, guided self‐help, treatment, relapse prevention, and carer support. Results: A number of technology‐enhanced approaches have been developed for each facet of the care spectrum, and experiences that are reported with their implementation are overall promising. However, only few of them have been evaluated in adequately designed and powered trials. Discussion: This review suggests that technology‐enhanced interventions offer multiple opportunities to improve care for eating disorders. More research is needed on the efficacy, effectiveness, cost‐effectiveness, and reach of these approaches to ultimately estimate their public health impact. It is discussed to what extent innovative models of care integrating technology‐enhanced interventions and face‐to‐face interventions may improve service delivery for eating disorders. © 2013 by Wiley Periodicals, Inc. (Int J Eat Disord 2013; 46:508–515)